Adaptations in Visual Search Behaviour as a Function of Expertise in Rugby Union Players Completing Attacking Scenarios - van Paridon, Kjell N.; Lally, J.; Robertson, P. J.; Basevitch, Itay; Timmis, Matthew A. (Frontiers in Psychology, 2022)
The current study investigated the adaptations which occur in visual search behaviour as a function of expertise in rugby union players when completing attacking scenarios. Ten experienced players and ten novice players completed 2 vs. 1 attacking game scenarios. Starting with the ball in hand and wearing a mobile eye tracker throughout, participants were required to score a try against a defender. The scenarios allowed for a pass to their supporting player (Spin Pass or Switch) or trying to run past the defender (Take-Player-On or Dummy Switch). No between group differences were found in fixating on the supporting attacking player (p>.05). However, experienced players increased the length (p=.008) and frequency (p=.004) looking at the area immediately ahead of the supporting player, particularly when executing a spin pass. Novice players fixated longer (p=.005) and more frequently (p=.032) at the defender, whilst experienced players fixated more frequently in the space the supporting player would run into in Switch and Dummy Switch scenarios (p=.025). More successful passes were completed and tries scored by experienced players compared to novice players (p=.001). Differences in visual search behaviour between experienced and novice players suggest that the experts extract information from areas directly related to guiding the motor action; the space immediately ahead of the support player to pass the ball in. Contrastingly, novices use a more allocentric perspective where the actions from the defender are used to guide their motor actions.